2010
DOI: 10.1177/0042098010379279
|View full text |Cite
|
Sign up to set email alerts
|

Housing Estates in the Czech Republic after Socialism

Abstract: The main purpose of this paper is to identify ongoing changes in post-socialist large housing estates and to clarify their main factors, using a case study approach. The paper examines the transformations of nine housing estates in the third largest Polish city -Łódź. The transformations were analysed in two dimensions: social (socio-demographic changes) and physical (changes in the spatial and functional structure and changes in the physiognomy). The key question was whether the changes occurring in large hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(44 citation statements)
references
References 45 publications
4
30
1
3
Order By: Relevance
“…In large housing estates, ageing is the result of limited residential mobility, and, for that reason, the period in which an estate originated is signifi cant for the development of an estate community. The results of the analysis confi rmed the conclusions of research conducted in the post-socialist housing estates by other authors [Kabisch and Grossmann 2013;Temelová et al 2011], who found that the ageing process was the result of the distribution of fl ats to people in a selected age group when the estate was built. The ageing of the communities in the housing estates means that the infrastructure needs to be adjusted to the needs of the elderly-for example, by installing access lifts in fi ve-storey buildings or remodelling public services.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In large housing estates, ageing is the result of limited residential mobility, and, for that reason, the period in which an estate originated is signifi cant for the development of an estate community. The results of the analysis confi rmed the conclusions of research conducted in the post-socialist housing estates by other authors [Kabisch and Grossmann 2013;Temelová et al 2011], who found that the ageing process was the result of the distribution of fl ats to people in a selected age group when the estate was built. The ageing of the communities in the housing estates means that the infrastructure needs to be adjusted to the needs of the elderly-for example, by installing access lifts in fi ve-storey buildings or remodelling public services.…”
Section: Discussionsupporting
confidence: 82%
“…The process of ageing of large housing estates was analysed in some comparative studies on European cities [Filius and van Kempen 2005;Dekker et al 2011] and on some Central and Eastern European cities [Kabisch and Grossmann 2013;Temelová and Slezáková 2014]. The ageing of estates relates to the time when estates were built and to the fact that estates fl ats were mainly assigned to young families [Kährik and Tammaru 2010;Temelová et al 2011;Kabisch and Grossmann 2013].…”
Section: Research On Large Housing Estates: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Tradičně je mezi "nevyhraněnými" lokalitami (sociálně-prostorovými formacemi) věnována významná pozornost panelovým sídlištím, kde byl na základě srovnání s vývojem urbanisticky a architektonicky podobných čtvrtí v západní Evropě předpokládán rychlý úpadek -zhoršování fyzické-ho stavu a pokles sociálního statusu obyvatel. Empirické výzkumy sice ukazují určitý pokles sociálního statusu (zejména vzdělanosti) v agregátu sídlišť, zároveň však konstatují rozmanitost trajektorií sídlišť v různých městských a regionálních kontextech [Temelová et al 2011], a to jako možný důsledek kombinace řady ekonomických i kulturních faktorů [Špaček 2012].…”
Section: Rezidenční Segregace Sociálněprostorové Formace a Obecní Byunclassified